Factors influencing the acceptance of augmented reality in education: a review of the literature - Che Dalim, Che Samihah; Kolivand, Hoshang; Kadhim, Huda; Sunar, Mohd Shahrizal; Billinghurst, Mark (Science Publication, 2017)
This paper presents a review of user expectation towards Augmented Reality (AR) and the acceptance of AR for technologyenhanced teaching and learning. Augmented Reality is a technology that superimposes a computer-generated image over a user’s view of the real world, thus providing a composite view. This technology has been used in many fields such as marketing, military, entertainment and many other sectors. Studies have found that AR technology can enhance teaching and learning, however more research still needs to be conducted about the acceptance of AR as a learning tool and what users in education expect from the technology. An understanding of the user expectation is one of the key foundations towards establishing better-designed AR systems and applications that will result in more acceptance of this technology. To help with this, this paper reviews previous research on user expectations of AR in education and its acceptance.